2005
DOI: 10.1371/journal.pmed.0020343
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Activation of Virus-Specific CD8+T Cells after Acute B19 Infection

Abstract: BackgroundHuman parvovirus B19 (B19) is a ubiquitous and clinically significant pathogen, causing erythema infectiosum, arthropathy, transient aplastic crisis, and intrauterine fetal death. The phenotype of CD8+ T cells in acute B19 infection has not been studied previously.Methods and FindingsThe number and phenotype of B19-specific CD8+ T cell responses during and after acute adult infection was studied using HLA–peptide multimeric complexes. Surprisingly, these responses increased in magnitude over the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 40 publications
9
75
1
2
Order By: Relevance
“…Longitudinal studies akin to the mouse models have been somewhat hard to establish in CMV, but parvoviruses B1936, 37 and more recently PARV438, 39 can be tracked following acute infection in adults and responses to specific epitopes show similar features of delayed expansion associated with maintained effector‐memory phenotypes and sustained functionality. Parvoviruses, such as these, do not undergo a latency programme, but can establish a long‐term DNA pool in tissues, and—if the T cells are to be trusted—these data indicate long‐term epitope production.…”
Section: What Is Memory Inflation Now?mentioning
confidence: 99%
“…Longitudinal studies akin to the mouse models have been somewhat hard to establish in CMV, but parvoviruses B1936, 37 and more recently PARV438, 39 can be tracked following acute infection in adults and responses to specific epitopes show similar features of delayed expansion associated with maintained effector‐memory phenotypes and sustained functionality. Parvoviruses, such as these, do not undergo a latency programme, but can establish a long‐term DNA pool in tissues, and—if the T cells are to be trusted—these data indicate long‐term epitope production.…”
Section: What Is Memory Inflation Now?mentioning
confidence: 99%
“…Genetic variability in the cytokine response has been associated with the likelihood of developing symptoms during B19V infection (46). A remarkably prolonged activation of virus-specific CD8 ϩ T cells has been observed after acute B19V infection (40). Recently, productive B19V infection of endothelial cells has been obtained in vitro (77), and the stimulation and/or persistent infection of such cells could play a role in the pathogenesis of the virus (23).…”
Section: Immunological Dysfunctionsmentioning
confidence: 99%
“…Although limited data are available, studies have shown a striking CD8 ϩ T cell response mounted predominantly against B19 NS1 (31). Moreover, activated CD8 ϩ T cells against B19 epitopes have been detected for up to 2 yr after infection, which may suggest that T cells contribute to long-term pathogen control (32). It is interesting that Isa et al (33) showed a discordance between the distribution of the cellular immune response in healthy seropositive individuals compared with those with B19 persistence with skewing of the CD8 ϩ T cell response toward structural VP proteins in the latter.…”
Section: Pathogenesis and Immune Responsementioning
confidence: 99%